2012
DOI: 10.1111/j.1469-0691.2011.03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Q fever and spontaneous abortion

Abstract: Q fever, caused by Coxiella burnetii, may result in abortions in infected animals and pregnant women. However, the role that Q fever plays in spontaneous abortions is still unknown. This study examined the association between Q fever serology and abortion in a region where Q fever is endemic. A case-control population-based study was conducted in General Yagüe Hospital (Burgos area, Spain) between June 2009 and July 2010. A total of 801 samples from 500 pregnant women were tested, of whom 273 had a spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…In a study conducted on 500 pregnant women, Quijada et al [8], found seropositivity as 32.2% in the 273 women with a history of spontaneous abortion, while in the control group it was found as 23.3% (p˂0.01). As a result of this study, it was concluded that active or the recent Q fever infection is associated with the risk of abortion.…”
Section: Discussionmentioning
confidence: 95%
“…In a study conducted on 500 pregnant women, Quijada et al [8], found seropositivity as 32.2% in the 273 women with a history of spontaneous abortion, while in the control group it was found as 23.3% (p˂0.01). As a result of this study, it was concluded that active or the recent Q fever infection is associated with the risk of abortion.…”
Section: Discussionmentioning
confidence: 95%
“…The First in the context of valvular endocarditis [13,14], and the other by infection of vascular atherosclerotic plaques. This second mechanism has not been tested, but this action is not only biologically plausible [16][17][18], but also probable [15]. Furthermore, the presence of this mechanism could explain some of our results; as independence showing this association with the presence of cardioembolic focus.…”
Section: Discusionmentioning
confidence: 87%
“…This addition to the group of potential pathogens involved in cerebrovascular disease is fully justified. If it is due to a germ of intracellular growth [16], it can persist in the body for long periods of time [14], reactivated in case of immunosuppression [16] or pregnancy [17], and promote inflammation, thrombosis and embolus in vascular beds [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Q fever endocarditis can occur months to years after the primary infection, particularly in people with cardiovascular abnormalities (Raoult et al., ; Million and Raoult, ; Million et al., ). Additionally, QF can result in premature pregnancy termination or complications in pregnant women (Quijada et al., ; Million and Raoult, ).…”
Section: Introductionmentioning
confidence: 99%